2021
DOI: 10.3390/ijms22147249
|View full text |Cite
|
Sign up to set email alerts
|

Liver Injury and the Macrophage Issue: Molecular and Mechanistic Facts and Their Clinical Relevance

Abstract: The liver is an essential immunological organ due to its gatekeeper position to bypassing antigens from the intestinal blood flow and microbial products from the intestinal commensals. The tissue-resident liver macrophages, termed Kupffer cells, represent key phagocytes that closely interact with local parenchymal, interstitial and other immunological cells in the liver to maintain homeostasis and tolerance against harmless antigens. Upon liver injury, the pool of hepatic macrophages expands dramatically by in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 183 publications
(223 reference statements)
1
43
0
Order By: Relevance
“…The disease state and the differentiation status of macrophages are crucial to determine whether macrophages are playing a pro-fibrotic role or, in contrast, exerting anti-fibrogenic activity [94]. In this case, as previously described, it has been extensively demonstrated in murine models that macrophages of the Ly6C low phenotype contribute to collagen breakdown and regression of ECM deposition [96,109,127]. An example of macrophages that have this phenotype are CD11b high /F4/80 intermediate LY6C low macrophages [95].…”
Section: Macrophages In Liver Fibrosismentioning
confidence: 90%
See 2 more Smart Citations
“…The disease state and the differentiation status of macrophages are crucial to determine whether macrophages are playing a pro-fibrotic role or, in contrast, exerting anti-fibrogenic activity [94]. In this case, as previously described, it has been extensively demonstrated in murine models that macrophages of the Ly6C low phenotype contribute to collagen breakdown and regression of ECM deposition [96,109,127]. An example of macrophages that have this phenotype are CD11b high /F4/80 intermediate LY6C low macrophages [95].…”
Section: Macrophages In Liver Fibrosismentioning
confidence: 90%
“…[128] TREM2+CD9+ MMP-13 Fibrosis resolution and inflammation restoration through MIF [129,130] SAMs MMP-2 and MMP-14 increase and TIMP-1 and TIMP-2 inhibition Fibrosis resolution [131] Ly6C high ↓ Ly6C low STAT-3-IL-10-IL-6 axis Switching from the pro-fibrotic Ly6C high phenotype to the pro-restorative Ly6C low [133] PtdSer-dependent RTKs and MERTK [134] CD5L [135] stabilin-1 [136] Interestingly, certain murine model studies have revealed the possibility of switching from the pro-fibrotic Ly6C high phenotype to the pro-restorative Ly6C low through different molecular pathways [96]. One of the most described pathways involves the STAT-3-IL-10-IL-6 axis [133].…”
Section: Cb1mentioning
confidence: 99%
See 1 more Smart Citation
“…However, this traditionally classification based on induction of in vitro polarization does not well describe the phenotypic heterogeneity of hepatic macrophage in vivo [109]. In murine models, Ly6c expression is used to characterize populations of circulating monocytes and macrophages in pathology [119,122]. Circulating Ly6c + / high and Ly6c − / low monocytes have been well characterized.…”
Section: Macrophagesmentioning
confidence: 99%
“…KCs express specific markers useful for their characterization, such as F4/80, CD11b +/low , CD68 and, C-type lectin domain family 4 member F (CLEC4F) in mice [122]. In the early stages of liver damage, KCs exert proinflammatory and protective actions, through the release of cytokines and chemokines, which further recruit other immune cells.…”
Section: Embryologically-derived/resident Macrophagesmentioning
confidence: 99%